The Recovery of the Waste Cigarette Butts for N-Doped Carbon Anode in Lithium Ion Battery - Yu, Chengyi; Hou, Hongying; Liu, Xianxi; Han, Lina; Yao, Yuan; Dai, Zhipeng; Li, Dongdong (Frontiers in Materials, 2018)
As one of the common life garbages, about 4.5 trillion waste cigarette butts are produced and randomly discarded every year due to the addiction to the nicotine and the need of the social intercourse. Such a treatment would result in the waste of the resources and the environmental pollution if they weren’t reasonably recycled in time. Herein, the waste cigarette butts were recycled in form of N-doped carbon powders with high economic value-added via one-step facile carbonization at 800 °C for 2 h in the inert N2 atmosphere. The waste-cigarette-butts-derived black carbon powders were characterized by scanning electron microscope (SEM), N2 adsorption/desorption and X-ray photoelectron spectroscopy (XPS). Furthermore, the corresponding electrochemical performances as the anode in lithium ion battery (LIB) were also investigated by galvanostatic charge/discharge, cyclic voltammetry (CV) and alternating current (AC) impedance. The results suggested that the recycled N-doped waste cigarette butts carbon (WCBC) powders consisted of major carbon and minor residual N-containing and O-containing functional groups, and the corresponding specific surface area was about 1285 m2•g-1. Furthermore, and the reversible specific discharge capacity was about 528 mAh•g-1 after 100 cycles at 25 mA•g-1 and about 151 mAh•g-1 even at 2000 mA•g-1 for 2500 cycles. Additionally, full cell performances were also satisfactory, indicating high feasibility. N-doping induced more active sites and higher electronic conductivity, and the resultant synergistic effect may be responsible for the satisfactory electrochemical performances, which offered good inspiration and strategy to develop the green energy and circular economy.